Inter-fibrillar tie chains determined critical stress of large strain cavitation in tensile stretched isotactic polypropylene. (28th February 2018) - Lu, Ying; Lyu, Dong; Xiong, Bijin; Chen, Ran; Men, Yongfeng
Abstract: Isotactic polypropylene (iPP) samples with pure mesophase, pure α modification, and coexistence of both phases were used to investigate the sudden stress whitening triggered at large strain during stretching. This whitening was caused by the cavities generated in the highly oriented amorphous network. The critical stresses of such cavitation-induced whitening were found to depend on the crystalline morphology before stretching. Below the phase transition temperature of mesophase to α phase, iPP sample with mesophase presented the highest critical stress of cavitation-induced whitening at large strain upon stretching while the one with α crystallites gave the smallest critical stress value. iPP sample with coexistence of both phases showed an intermediate critical stress of cavitation-induced whitening. However, these critical stresses of cavitation-induced whitening in the iPP samples, which experienced the mesophase to α phase transition before stretching, started to decrease under deformation above the corresponding phase transition temperature. This peculiar evolution of the critical stress for initiating cavitation-induced whitening in iPP samples at large strain could be understood by the change of number of load bearing inter-fibrillar tie chains within the highly oriented inter-fibrillar amorphous network at different conditions. Graphical abstract: Highlights: Breakage of load bearing inter-fibrillar tie chains initiates cavitation induced stress whitening in iPP at large strains. Critical stress triggering such whitening depends on the initial morphologies that yield different density of load bearing tie chains. Change in the critical stress in mesophase sample is due to phase transition of mesophase to α phase at 80 o C before deformation.